To solve this system of equations by substitution, we can substitute the expression for y in the first equation with the expression given for y in the second equation.
6x + 3(2x + 5) = 39
6x + 6x + 15 = 39
12x + 15 = 39
12x = 24
x = 2
Now that we have found x=2, we can substitute it back into the second equation to find y.
y = 2(2) + 5
y = 4 + 5
y = 9
Therefore, the solution to the system of equations is (2, 9). So the correct answer is (2, 9).
Solve the system of equations by substitution. 6x+3y=39 6 ��� + 3 ��� = 39 y=2x+5 ��� = 2 ��� + 5 %C2%A0 (1 point) Responses (−9,−2) ( − 9 , − 2 ) open paren negative 9 comma negative 2 close paren (6,%C2%A02) ( 6 , %C2%A0 2 ) (6,%C2%A02) ( 6 , %C2%A0 2 ) (6,%C2%A04) ( 6 , %C2%A0 4 ) (6,%C2%A04) ( 6 , %C2%A0 4 ) (2,9)
1 answer